Grammar teaching 91-19: an analysis of the portuguese curricula - Costa, Ana Luísa (2022)
The scope of the present study is the discourse about grammar, as a curriculum component, in the syllabi and learning outcomes for Basic and Secondary Education in force in Portugal from 1991 to 2019. The corpus includes thirteen curricular documents that conveyed the prescribed curriculum for Portuguese L1. A comparative study guides the analysis of the curricular discourse, focusing on three issues: (i) the concept of Grammar, (ii) the place of Grammar among other curriculum components, namely Speaking, Listening, Writing, and Reading, and (iii) the degree of explicitness in grammar instruction.Three dichot-omies (dependence / autonomy, prescriptivism / descriptivism, and language skills / reflective thinking), addressed in research, cross over the discourse about Grammar in the official documents. The results show different frames for Grammar conceptualizations, place and type of instruction, in a pathway from a dependent to an autonomous curricular component, and from instrumental goals to a balance between language skills enhancement and reflective activity.